157 ValiMP, a mixture of phytogenic compounds with manganese, reduces abdominal fat in broilers. (7th December 2018) - Choi, S; Park, M; Kwak, M; Lee, J; Whang, K
Abstract: The present study was conducted to determine the effects of dietary ValiMP ® (VMP) on growth performance and tissue characteristics in broilers. Previous studies have demonstrated that VMP, a mixture of phytogenic compounds with manganese, inhibited adipogenesis in 3T3-L1 preadipocytes, and promoted skeletal muscle hypertrophy in C2C12 myoblasts. However, its effects on growth, adipogenesis and myogenesis in broilers have yet been investigated. Therefore, a total of 240 1-day-old Ross 308 broilers were randomly assigned to one of the 4 treatments with 5 replications. Dietary treatments were 0% (CON), 0.125% (LV), 0.25% (MV), or 0.50% (HV) VMP supplemented to broiler diets, and the birds were fed the experimental diet for 35 days. At the end of the experiment, breast muscle, abdominal fat, and the liver were collected, and the statistical analyses were conducted by ANOVA procedure using SAS 9.3. Results showed that final body weight was increased in LV and MV treatments, with improved ADG in LV treatment compared to CON (p<0.10). Tissue weight and mRNA levels of myogenic genes in breast muscle were not affected by dietary treatments. However, abdominal fat weight (mg/g body weight) was significantly decreased in HV treatment compared to the other treatments (p<0.10). Moreover, mRNA levels of acetyl-CoA carboxylase in abdominal fat were suppressed by 63%, 43%, and 55% in LV, MV, and HV treatments, respectively, compared to CON (p<0.10). mRNA levels of fatty acid synthase ( FAS ) in all VMP treatments were reduced in a similar manner (p<0.10). Although liver weight did not differ among treatments, hepatic mRNA levels of FAS and sterol regulatory element-binding protein 1 were downregulated by 70% in all VMP treatments compared to CON (p<0.05). Overall, results indicate that ValiMP supplementation in broiler diet was effective in reducing abdominal fat by suppressing mRNA levels of adipogenic genes in adipose tissue and the liver.